SCRUTINIZING ENGLISH DISCOURSE MARKERS IN EFL STUDENTS’ WRITING PRODUCTION - Listyaning Sumardiyani; Dias Andris Susanto (Universitas PGRI Semarang, 2020)
Fraser (1988; 1996; 1999) which are classified EDMs functions as ‘contrastive, ‘elaborative, and ‘inferential. This study designated the use of English discourse markers by University EFL students in writing production. To answer the research question on how do they disclose EDMs in producing writing, the writers employed a qualitative research approach. The object was the documentation of students’ writing result mediated on the writing class. The participants were 38 students of semester III in the academic year 2018/2019. The findings are the contrastive markers are; but 63/instead of 2/whereas 2/however 16/although 2/in the other hand /side 6. The elaborative markers are; and 597/also 105/or 69/for example 27/besides 7/moreover 3/in addition, 24/then 6/likewise 1. The inferential markers are; because 97/so 51/as a result 9/therefore 11/in conclusion 3/then 1. The most functions of discourse markers use by students are; the marker ‘but’ has a meaning ‘on the contrary. The marker ‘and’ has a meaning as ‘in addition’. Students used the marker ‘because’ to indicate ‘for the reason’. The implication of this study is that students need to understand in employing properly English discourse markers to make their writing being cohesive and coherent in texts.